Composition, physico-chemical properties and antioxidant capacity of Renealmia alpinia (Rottb.) Maas fruit - Luna Guevara, María Lorena (2018)
Composition and bioactive properties of x`kijit fruit [ Renealmia alpinia (Rottb.) Maas] pulp and peel is unknown so far . Therefore, the objective of this study was to evaluate physicochemical, and nutritional characteristics, bioactive compounds and antioxidant activity of peel, pulp of the fruit (x`kijit fruit). The fruit pulp was higher in soluble solids (10.53°Brix) and pH (6.2), while the peel had lower pH (3.9) and soluble solids (2.3°Brix). The protein and fat contents were higher in pulp with values 4.2 and 8.6%, respectively. Vitamin C, flavonoids, phenolic compounds, and carotenoids were higher in pulp (28.3 mg ascorbic acid.100 g -1 FW, 567.8 mg catechin.100 g -1 FW, 102.4 mg GAE.100 g -1 FW, and 332 μg of carotenoid.100 g -1 FW, respectively) than peel. However, the peel was higher in anthocyanins (181.4 mg of cyanidin.100 g -1 FW), yielding an antioxidant activity of 23.3mMFe 2+ .100 g -1 . The x`kijit fruit demonstrated to have an important nutritional composition and a high antioxidant activity.